2014
DOI: 10.1038/ncomms4693
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Experience enhances gamma oscillations and interhemispheric asymmetry in the hippocampus

Abstract: The gamma-filtered traces of the image in Fig. 3a were inadvertently duplicated from Fig. 2a. In addition, the legend for Fig. 3 incorrectly stated that slow gamma traces were displayed in Fig. 3a. In fact, these traces do not distinguish between fast and slow recordings. The correct version of the figure and its legend appear below. The slow and fast gamma power ratios of ENR þ ket were significantly lower than 1 (*Po0.05 and **Po0.01, respectively, t-test, N ENR ¼ 10,The ENR and ENR þ ket power ratios were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…We start with a complex domain state of primarily out-of-plane polarized domains, with contributions of the interfaces and needle-like domains. This mixed state with upwards and downwards polarization domains is comparable to the non-switchable PZT domains previously reported by Han et al [ 11 ]. At 5 s, we start increasing the voltage by 1 V/s.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…We start with a complex domain state of primarily out-of-plane polarized domains, with contributions of the interfaces and needle-like domains. This mixed state with upwards and downwards polarization domains is comparable to the non-switchable PZT domains previously reported by Han et al [ 11 ]. At 5 s, we start increasing the voltage by 1 V/s.…”
Section: Resultssupporting
confidence: 89%
“…Over the last decade, major insights into the nanoscale processes involved in ferroelectric switching were driven by the development of specialized transmission electron microscopy (TEM) systems for in situ experiments using a conductive nano-sized probe brought into contact with the specimen using a piezo-micromanipulator [ 8 , 10 , 11 , 12 , 13 , 14 , 15 ]. The importance of interfaces and their associated defects were confirmed by combining these holders with atomic resolution scanning TEM (STEM) imaging as well as conventional dark-field TEM [ 10 , 11 ]. It was further shown that ferroelastic domains can be permanently stabilized by dislocations at the substrate interface, while similar domains without such pinning dislocations can behave more freely [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, an accumulation of defects at specific interfaces deteriorates the overall behaviour of polarization-switching dynamics 20 , 21 . For the charged domain walls stabilized by oxygen vacancies, the defect kinetics determine the switching process that is accompanied by a vacancy redistribution 22 , 23 , and thereby the device operation speed is limited by vacancy transport times 22 .…”
Section: Introductionmentioning
confidence: 99%
“…For the charged domain walls stabilized by oxygen vacancies, the defect kinetics determine the switching process that is accompanied by a vacancy redistribution 22 , 23 , and thereby the device operation speed is limited by vacancy transport times 22 . The strong interaction with the vacancies gives rise to the clamping of domain walls 24 – 27 and eventually causes imprint, retention loss, and fatigue of polarization states, preventing the widespread use of ferroelectric-based memories 1 , 21 , 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%